Estimation of fast vagal response by time-dependent analysis of heart rate variability in normal subjects - Keselbrener, L; Baharav, A; Akselrod, S (Clinical autonomic research, 1996)
In this study, the selective windowed discrete Fourier transform algorithm (SDA) for time-frequency analysis was applied on non-stationary heart rate signals, recorded during vagal perturbations. These perturbations were achieved in healthy subjects (aged 6-42 years) by inducing the oculocardiac reflex and the diving response. The results showed that the SDA can detect and quantify the expected, although brief, increase in vagal tone, by displaying a marked transient increase in the respiratory peak of the time-dependent spectrum. It allowed us to demonstrate an age-dependent reduction of the vagal response, obtained from the respiratory peak of the heart rate time-dependent spectrum. The SDA approach is thus an adequate tool for the evaluation of an instantaneous change in vagal activity, as well as steady-state vagal activity, including the detection of a malfunction or an exaggerated response of the parasympathetic tone. Since changes in heart rate control are expressed by a transient response, they would not have been detected by a standard, steady-state spectral analysis of heart rate variability, which requires the consideration of long and steady trace lengths and would therefore cause smearing of such fast changes. Time-dependent, or transient changes in autonomic control can thus be detected and quantified by SDA time-frequency analysis.